Dampak Struktur Modal, Likuiditas, dan Profitabilitas Terhadap Nilai Perusahaan pada Perusahaan Makanan dan Minuman - Safitri, Ari Sarwo Indah; Azhari, Sri Rahayu Indah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to examine the effect of capital structure, liquidity, and profitability on firm value in food and beverage companies listed on the Indonesia Stock Exchange (IDX). The data for this research was obtained from the financial statements of food and beverage companies registered on the IDX. This research employs secondary data collected through observations by visiting the Capital Market Information Center (PIPM). The data analysis method used is multiple linear regression analysis. The results of the study show that, partially, capital structure, liquidity, and profitability have a negative and significant impact on firm value.